Factors influencing elderly women's mammography screening decisions: implications for counseling - Schonberg, Mara A (BioMed Central, 2007)
BACKGROUND: Although guidelines recommend that clinicians consider life expectancy before screening older women for breast cancer, many older women with limited life expectancies are screened. We aimed to identify factors important to mammography screening decisions among women aged 80 and older compared to women aged 65–79. METHODS: Telephone surveys of 107 women aged 80+ and 93 women aged 65–79 randomly selected from one academic primary care practice who were able to communicate in English (60% response rate). The survey addressed the following factors in regards to older women's mammography screening decisions: perceived importance of a history of breast disease, family history of breast cancer, doctor's recommendations, habit, reassurance, previous experience, mailed reminder cards, family/friend's recommendations or experience with breast cancer, age, health, and media. The survey also assessed older women's preferred role in decision making around mammography screening. RESULTS: Of the 200 women, 65.5% were non-Hispanic white and 82.8% were in good to excellent health. Most (81.3%) had undergone mammography in the past 2 years. Regardless of age, older women ranked doctor's recommendations as the most important factor influencing their decision to get screened. Habit and reassurance were the next two highly ranked factors influencing older women to get screened. Among women who did not get screened, women aged 80 and older ranked age and doctor's counseling as the most influential factors and women aged 65–79 ranked a previous negative experience with mammography as the most important factor. There were no significant differences in preferred role in decision-making around mammography screening by age, however, most women in both age groups preferred to make the final decision on their own (46.6% of women aged 80+ and 50.5% of women aged 65–79). CONCLUSION: While a doctor's recommendation is the most important factor influencing elderly women's mammography screening decisions, habit and reassurance also strongly influence decision-making. Interventions aimed at improving clinician counseling about mammography, which include discussions around habit and reassurance, may result in better decision-making.